Is 18F-FDG-PET suitable to predict clinical response to the treatment of geriatric depression? A systematic review of PET studies. (2nd September 2017) - De Crescenzo, Franco; Ciliberto, Mario; Menghini, Deny; Treglia, Giorgio; Ebmeier, Klaus P.; Janiri, Luigi
ABSTRACT: Background: Geriatric depression is one of the most common psychiatric disorders in later life. It differs from earlier depression in its presentation, etiology, risk factors, protective factors and outcome. Positron emission tomography (PET) can be used to detect changes in neural circuitry in neuropsychiatric disorders, and several authors have assessed its role in the diagnosis and follow-up of patients with geriatric depression. We reviewed the current evidence on the use of fluorine-18-fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET) in geriatric depressed patients to find predictors of treatment response. Methods: We searched PubMed/MEDLINE, Scopus, Embase, Cochrane Library, CINAHL and the PsycINFO databases to find relevant peer-reviewed articles on PET in geriatric depression using the search terms ('PET' or 'positron emission tomography') and ('mood' or 'affective disorder' or 'affective disorders' or 'depression' or 'dysthymia' or 'seasonal affective disorder'). Results: Eleven articles comprising 128 patients were included. We extracted data on glucose uptake of depressed patients and controls at baseline and after different types of intervention (total sleep deprivation followed by a recovery sleep and treatment with selective serotonin reuptake inhibitors). Conclusions: 18 F-FDG-PET showed significant alterations of glucose uptake in several brain areas, in particular the anterior cingulate cortex, which showed reduced metabolism after treatment, and was a predictor of treatment response.